2015
DOI: 10.1002/2015gl066668
|View full text |Cite
|
Sign up to set email alerts
|

Crustal architecture beneath the Tibet‐Ordos transition zone, NE Tibet, and the implications for plateau expansion

Abstract: Most previous studies of the Tibetan Plateau have focused on the processes of crustal thickening and subsequent outward growth. However, lithospheric structure across the tectonic boundaries of the plateau has not yet been fully imaged, and therefore, how geological structures evolved in association with the lateral expansion of the margins remains unclear. Here together with interpretation of regional aeromagnetic anomalies, we employ a recently acquired 165 km long deep seismic reflection image that crosses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…This mechanism seems analogous with the observed scenario in the Tibet‐Sichuan transition zone, namely, the Longmenshan area (Liu et al, ; Zhang et al, ). This mechanism is distinguishable, however, from those responsible for the uplift within the Tibet‐Ordos and Tibet‐Alxa transition zones that significantly depend upon upper crustal shortening processes above a weak midcrustal decollement (Gao et al, ; Guo et al, , ; Ye et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism seems analogous with the observed scenario in the Tibet‐Sichuan transition zone, namely, the Longmenshan area (Liu et al, ; Zhang et al, ). This mechanism is distinguishable, however, from those responsible for the uplift within the Tibet‐Ordos and Tibet‐Alxa transition zones that significantly depend upon upper crustal shortening processes above a weak midcrustal decollement (Gao et al, ; Guo et al, , ; Ye et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated from the 165 km-long deep seismic reflection profile (dashed purple line in Fig. 1), the ductile shear zone bounding the conveyor belt at its base subsequently extends beneath the Liupan Shan belt, causing shallow deformation within the Tibet-Ordos transition zone Guo et al, 2015). The sedimentary features separating the Mariana-type arc basement from the Ordos block in the north-easternmost Tibet are structurally inadequate to the crustal loading.…”
Section: Deformation Pattern and Regional Kinematicsmentioning
confidence: 98%
“…The contractional transition zone experience rapid uplift at ∼8 Ma (Zheng et al, 2006) and expanded eastward causing the Xiaoguan Shan uplift at ∼5 Ma . Meanwhile, the intervening sediments beneath the Tibet-Ordos transition zone compressed against the underlying Moho layer Guo et al, 2015). Horizontal orientation of strata in the Xiaoguan Shan indicates that deformation related to plateau extrusion does extend least to that feature .…”
Section: Deformation Pattern and Regional Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The southwestern Ordos block is physiographically linked to the Liupanshan Mountains (LPSM) to the north and constitutes an important part of the Weihe graben (WHG) to the south (Figure a). Previous studies have shown that the LPSM absorbs nearly east‐west crustal shortening, characterized by thrust faulting and folding (e.g., Guo et al, ; Zhang et al, , ). In contrast, the WHG is dominated by northwest‐southeast extension and hosts active normal faults (e.g., State Seismological Bureau, ; Zhang et al, , ).…”
Section: Introductionmentioning
confidence: 99%